‘I Think Women are Possibly Judged More Harshly with Comedy’: Women and British Television Comedy Production - Mills, Brett; Ralph, Sarah (Critical Studies in Television, 2015)
Critics and creative workers have recently highlighted the lack of women working in British television comedy. Through thematic analysis of interviews with British television comedy professionals, this article explores how women talk about their work and their position within the industry. Outlining the specific industrial contexts within which female comedy professionals work, the article examines institutionalised gender norms and practical impediments which the interviewees' responses reveal, while also exploring the institutional and personal initiatives which they have developed to address these problems.